Test-Retest Reliability of the Binaural Interaction Component of the Auditory Brainstem Response. Issue 5 (September 2016) - Ferber, Alexander T.; Benichoux, Victor; Tollin, Daniel J.
Abstract : Objectives: The binaural interaction component (BIC) is the residual auditory brainstem response (ABR) obtained after subtracting the sum of monaurally evoked from binaurally evoked ABRs. The DN1 peak—the first negative peak of the BIC—has been postulated to have diagnostic value as a biomarker for binaural hearing abilities. Indeed, not only do DN1 amplitudes depend systematically upon binaural cues to location (interaural time and level differences), but they are also predictive of central hearing deficits in humans. A prominent issue in using BIC measures as a diagnostic biomarker is that DN1 amplitudes not only exhibit considerable variability across subjects, but also within subjects across different measurement sessions. Design: In this study, the authors investigate the DN1 amplitude measurement reliability by conducting repeated measurements on different days in eight adult guinea pigs. Results: Despite consistent ABR thresholds, ABR and DN1 amplitudes varied between and within subjects across recording sessions. However, the study analysis reveals that DN1 amplitudes varied proportionally with parent monaural ABR amplitudes, suggesting that common experimental factors likely account for the variability in both waveforms. Despite this variability, the authors show that the shape of the dependence between DN1 amplitude and interaural time difference is preserved. The authors then provide a BIC normalization strategy using monaural ABR amplitude that reduces the variability of DN1 peak measurements. Finally, the authors evaluate this normalization strategy in the context of detecting changes of the DN1 amplitude-to-interaural time difference relationship. Conclusions: The study results indicate that the BIC measurement variability can be reduced by a factor of two by performing a simple and objective normalization operation. The authors discuss the potential for this normalized BIC measure as a biomarker for binaural hearing. Abstract : The binaural interaction component (BIC) of the auditory brainstem response (ABR) is an electrical measure of binaural processing in the auditory brainstem, which exhibits considerable variability across normal hearing subjects and measurement sessions. In repeated measurements of the BIC in adult guinea pigs, BIC amplitudes varied proportionally with ABR amplitudes. Normalizing BICs to ABR amplitude, the variability across and within subjects reduced two-fold, while preserving dependence on binaural cues. This method enables the possibility of using the BIC as a diagnostic tool probing central auditory deficits.